The clinical and molecular landscape of diffuse hemispheric glioma, H3 G34-mutant - Le Rhun, Emilie; Bink, Andrea; Felsberg, Joerg; Gramatzki, Dorothee; Brandner, Sebastian; Benhamida, Jamal K; Wick, Antje; Tonn, Joerg C; Mohme, Malte; Tabatabai, Ghazaleh; Capper, David; Snuderl, Matija; et al. (Neuro-Oncology, 2025)
Diffuse hemispheric glioma, histone 3 (H3) G34-mutant, has been newly defined in the 2021 World Health Organization (WHO) classification of central nervous system tumors. Here we sought to define the prognostic roles of clinical, neuroimaging, pathological, and molecular features of these tumors.We retrospectively assembled a cohort of 114 patients (median age 22 years) with diffuse hemispheric glioma, H3 G34-mutant, central nervous system WHO grade 4, and profiled the imaging, histological, and molecular landscape of their tumors.Compared with glioblastoma, H3 G34-mutant diffuse hemispheric gliomas exhibited less avid contrast enhancement, necrosis, and edema on MRI. Comprehensive analyses of mutational and DNA copy number profiles revealed recurrent mutations in TP53 and ATRX, homozygous deletions of CDKN2A/B, and amplifications of PDGFRA, EGFR, CCND2, and MYCN. MGMT promoter methylation was detected in 79 tumors (75%); 11 tumors (13%) showed DNA copy number profiles suggestive of circumscribed deletions on 10q26.3 involving the MGMT locus. Median survival was 21.5 months. Female sex, gross total resection, and MGMT promoter methylation were positive prognostic factors on univariate analysis. Among radiological, pathological, and molecular features, the absence of pial invasion and the presence of microvascular proliferation and CDK6 amplification were positive prognostic factors on univariate analyses.This study refines the clinical and molecular landscape of H3 G34-mutant diffuse hemispheric gliomas. Dedicated trials for this novel tumor type are urgently needed.